Prevalence of depression in pregnant women attending the tertiary care center of rupandehi district: A cross sectional study - Kafle, Bikram; Bagale, Yashoda; Tiwari, Suraj; Pandey, Niraj; Thakur, Nishant Kumar (Journal of Psychiatrists' Association of Nepal, 2024)
Introduction: Depression during pregnancy can have serious health consequences on maternal and child health. It is one of the most prevalent mental disorders during pregnancy. The study aimed to find out the prevalence of depression in pregnant women attending the tertiary care center of Nepal. Methodology: We conducted a cross-sectional study among pregnant women visiting Antenatal clinic of Devdaha Medical College, Bhaluhi, Rupandehi, Nepal. Ethical approval was obtained from the Institutional Review Committee of same institute. Data was collected from Jan 2023 to June 2023.The calculated minimum required sample size was 128. The subjects were interviewed with Edinburgh Postnatal Depression Scale (EPDS). Results: Prevalence of depression was found to be 26.6%. Among depressed and non-depressed patients there was statistically significant difference in planned pregnancy (p<0.000), living with partner currently (p<0.001), and those with ideas of self harm (p<0.000). Conclusion: Around 26.56% of the sample population scored positive for antenatal depression which was comparable to the results obtained from other lower and middle-income countries. All those concerned with antenatal care need to pay attention and screen for depressive symptoms.